2023
DOI: 10.1002/jcop.22990
|View full text |Cite
|
Sign up to set email alerts
|

Formal youth mentoring relationships in the context of risk: What is the role of caregiver–mentor collaboration?

Abstract: Most research on youth mentoring relationships has focused on the mentor–mentee dyad, yet caregivers play an important role in supporting these relationships. Drawing on a large, multisite sample of youth in formal mentoring programs (N = 2165), this study investigated associations between caregiver–mentor collaboration and mentoring relationship outcomes in the context of environmental and individual youth risk factors. Analysis of novel quantitative measures assessing caregivers' experiences of the mentoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For example, Uebler et al (2023) investigated the dynamic processes of mentoring with the help of survival analyses and showed that changing patterns (e.g., a sudden change of frequency and focus shift from program content) of mentees' communication to mentors from 1 month to another predicted premature match closure. Parnes et al (2023) employed a design-based mediation analysis to examine caregivers' role in at-risk youths' mentoring relationships and found that the involvement of caregivers was associated with mentoring quality and match length. These results help program staff understand individual, contextual, and program-level factors contributing to the mentoring success and can provide guidance in the selection and matching processes, as well as program monitoring.…”
Section: Quality Assurance Of Mentoring Programsmentioning
confidence: 99%
“…For example, Uebler et al (2023) investigated the dynamic processes of mentoring with the help of survival analyses and showed that changing patterns (e.g., a sudden change of frequency and focus shift from program content) of mentees' communication to mentors from 1 month to another predicted premature match closure. Parnes et al (2023) employed a design-based mediation analysis to examine caregivers' role in at-risk youths' mentoring relationships and found that the involvement of caregivers was associated with mentoring quality and match length. These results help program staff understand individual, contextual, and program-level factors contributing to the mentoring success and can provide guidance in the selection and matching processes, as well as program monitoring.…”
Section: Quality Assurance Of Mentoring Programsmentioning
confidence: 99%